Differences in the approaches of cancer specialists toward adolescent and young adult cancer care. Issue 1 (26th May 2022) - Matsumoto, Kimikazu; Yamamoto, Kazuhito; Ozono, Seiichiro; Hashimoto, Hiroya; Horibe, Keizo
Abstract: Background: This study investigated the medical care of adolescent and young adult (AYA) cancer patients and compared approaches toward AYA cancer care by pediatric and adult cancer specialists. Methods: An Internet survey was conducted among 1, 305 specialists (192 pediatric and 1, 109 adult) in 2016. Results: The rate of awareness of the term "AYA" was lower for adult specialists than for pediatric specialists. The departments that are responsible for caring for AYA cancer patients change when they reach 20 years of age. For the treatment of AYA patients, both pediatric and adult specialists preferred a multidisciplinary team as a top priority issue. A special ward or hospital rooms for AYA was required mostly for AYA patients under 24, and the needs for special wards or rooms for AYA was higher in pediatric specialists than in adult specialists. However, for AYA patients over 25, about 60% of adult specialists and 35% of pediatric specialists believed that no special care was required. As for desirable follow‐up protocols for pediatric cancer AYA survivors, half of the specialists considered that they should be conducted mainly by pediatric specialists in cooperation with adult specialists, and 30% to 40% of the specialists considered that transition to the corresponding adult medicine department would be preferable. Conclusions: There were obvious differences in medical care and support for AYA cancer patients according to their age, particularly under the age of 20 or 24, and according to whether the onset of disease occurred during the AYA period or whether it was secondary to pediatric cancers. For each aspect, appropriate programs would require close cooperation between pediatric and adult specialists.